2015
DOI: 10.4314/sajas.v44i5.11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different dietary vitamin and mineral levels on certain production parameters, including egg shell characteristics of breeding ostriches

Abstract: Earlier studies on breeding birds indicated no effect of dietary energy-content on feed intake. This observation is contradictory to results for other animals and/or poultry where feed intake decreases with an increase in dietary energy level. Literature revealed that a lack of certain nutrients may cause animals to consume more feed than necessary to satisfy their nutrient requirements for these limiting nutrients. In this study eight diet groups were evaluated. A standard commercial diet plus one of the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…This supported the findings of [13] who reported that fish with adequate supplement apart from the main feed gain body weight faster. The result is also in line with the findings of [14] who observed better growth rate after supplementing their diet with 75% of egg shell.…”
Section: Discussionsupporting
confidence: 91%
“…This supported the findings of [13] who reported that fish with adequate supplement apart from the main feed gain body weight faster. The result is also in line with the findings of [14] who observed better growth rate after supplementing their diet with 75% of egg shell.…”
Section: Discussionsupporting
confidence: 91%